2002
DOI: 10.1073/pnas.232579599
|View full text |Cite
|
Sign up to set email alerts
|

The Usher syndrome proteins cadherin 23 and harmonin form a complex by means of PDZ-domain interactions

Abstract: Usher syndrome type 1 (USH1) patients suffer from sensorineuronal deafness, vestibular dysfunction, and visual impairment. Several genetic loci have been linked to USH1, and four of the relevant genes have been identified. They encode the unconventional myosin VIIa, the PDZ-domain protein harmonin, and the putative adhesion receptors cadherin 23 (CDH23) and protocadherin 15 (PCDH15). We show here that CDH23 and harmonin form a protein complex. Two PDZ domains in harmonin interact with two complementary binding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
266
2
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 216 publications
(281 citation statements)
references
References 42 publications
9
266
2
4
Order By: Relevance
“…Recently, Myo7a has been shown to interact with harmonin which in turn interacts with Cdh23 (Boeda et al 2002;Siemens et al 2002). All three proteins are present in the stereocilia, thus potentially placing Cdh23 and Myo7a in the same functional complex (Hasson et al 1997a;Boeda et al 2002).…”
Section: Age-related Hearing Lossmentioning
confidence: 99%
“…Recently, Myo7a has been shown to interact with harmonin which in turn interacts with Cdh23 (Boeda et al 2002;Siemens et al 2002). All three proteins are present in the stereocilia, thus potentially placing Cdh23 and Myo7a in the same functional complex (Hasson et al 1997a;Boeda et al 2002).…”
Section: Age-related Hearing Lossmentioning
confidence: 99%
“…The protocadherin LKC is associated with contact inhibition of cell proliferation, and has been suggested as a candidate TSG for colon and liver cancer (Okazaki et al, 2002). Mutations in protocadherin 15 as well as CDH23 have also been implicated in Usher syndrome (Bolz et al, 2001;Di et al, 2001;Siemens et al, 2002), as recently demonstrated in a zebrafish model Sollner et al, 2004).…”
Section: Introductionmentioning
confidence: 95%
“…Connections of a similar form, termed ankle links, occur transiently during the development of mammalian cochlear hair cells. Among several proteins whose deficiency produces Usher Syndrome, three have been proposed to constitute the ankle links: cadherin 23 (Di Palma et al 2001;Boeda et al 2002;Siemens et al 2002), the very large G-protein- In most receptor organs of the inner ear and lateralline system, mechanical stimuli representing sounds, accelerations, or water movements are initially conveyed to the kinocilium by an extracellular accessory structure. Connections of the second type, kinociliary links, then transmit these stimuli to the five longest stereocilia (Hillman and Lewis 1971).…”
Section: Introductionmentioning
confidence: 99%